Minimum wage systems (Geneva, 2014)
"The Committee of Experts on the Application of Conventions and Recommendations publishes annually an in-depth General Survey on member States' national law and practice, on a subject chosen by the Governing Body. This year the General Survey focuses on Minimum wage systems. General surveys are established mainly on the basis of reports received from member states and information transmitted by employers' and workers' organizations. They allow the Committee of Experts to examine the impact of conventions and recommendations, to analyse the difficulties indicated by governments as impeding their application or their ratification, and to identify means of overcoming these obstacles. "